“Lum Phi Fa” Worldviews of belief in the health care of Isan - Charoenmahavit, Benjapak (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
This article focuses on beliefs in Lam Pha Fah of the Isan people, based on their beliefs, therefore the Lam Pha Fah is used to maintain health. This study is a documentary research. The study found that The basis of this belief comes from respect for nature, spiritism, power, sacred things and belief in Buddhism. These beliefs have psychological effects. Resulting in good mental health and good encouragement to continue living.